2020
DOI: 10.1038/s41556-020-00582-w
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 controls cancer pyroptosis

Abstract: Programmed death ligand-1 (PD-L1) is well known for its role as an immune checkpoint regulator, but little is known about its function in other cellular processes. A study now shows that in tumour cells PD-L1 mediates pyroptosis, an inflammatory form of cell death, by activating the expression of Gasdermine c, ultimately leading to tumour necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Hou et al 70 found that antibiotic chemotherapy drugs could promote the combined effect of STAT3 and PD‐L1 to upregulate gasdermin C (GSDMC) under hypoxic conditions. It is worth noting that caspase‐8 can activate caspase‐3 to induce GSDMC‐mediated pyroptosis in breast cancer cells, 71 while STAT1 may also be associated with PD‐L1. Interestingly, it was also found that GSDMD and GSDME could directly induce pyroptosis, and that this mechanism is regarded as a significant biomarker that can predict the response to anti‐PD‐1 antibodies.…”
Section: Specific Relationship Between Pyroptosis and Immune Checkpointsmentioning
confidence: 99%
“…Hou et al 70 found that antibiotic chemotherapy drugs could promote the combined effect of STAT3 and PD‐L1 to upregulate gasdermin C (GSDMC) under hypoxic conditions. It is worth noting that caspase‐8 can activate caspase‐3 to induce GSDMC‐mediated pyroptosis in breast cancer cells, 71 while STAT1 may also be associated with PD‐L1. Interestingly, it was also found that GSDMD and GSDME could directly induce pyroptosis, and that this mechanism is regarded as a significant biomarker that can predict the response to anti‐PD‐1 antibodies.…”
Section: Specific Relationship Between Pyroptosis and Immune Checkpointsmentioning
confidence: 99%
“…The efficiency of anti-PD-1 or PD-L1 therapy can be improved under pyroptosis-induced inflammation in the tumor microenvironment by chemotherapy, radiotherapy, and other therapeutic regimens ( Bergsbaken et al, 2009 ; Reck et al, 2019 ). Published clinical trials have shown that antibiotic chemotherapeutics can promote the combination of STAT3 and PD-L1 to upregulate GSDMC mediated pyroptosis under hypoxia ( Blasco and Gomis, 2020 ), which may improve HCC patient survival compared to patients received only a single type of treatment to improve the efficiency of PD-L1 inhibitors. TIGIT, similar to LAG3, belongs to the immunoglobulin superfamily and is exclusively expressed on lymphocytes, including CD8 + T cells, memory, and regulatory CD4 + T cells, follicular CD4 + T cells, and NK cells ( Stanietsky et al, 2009 ; Ge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis can enhance antitumor immunity for its immunogenic nature 37 . Recently research demonstrates pyroptosis of tumor cells may overcome tumor cells’ apoptosis resistance and promotes antitumor immunity 38 , 39 . However, the specific mechanism of tumors pyroptosis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%